Korelasi antara kadar gula darah puasa dengan stress oksidatif dan aktivitas katalase pada tikus model diabetes melitus tipe 1 yang diterapi dengan MSC-WJ - Endrinaldi Endrinaldi (Majalah Kedokteran Andalas, 2023)
Objective: This study was conducted to investigate the involvement of oxidative damage in type 1 diabetes mellitus rats treated with Mesenchymal Stem Cell Wharton's Jelly (MSC-WJ) and to explain the correlation between fasting blood sugar levels and MDA levels as an indicator of oxidative stress and catalase activity.Methods: This research is experimental research with a Posttest-Only Control Group Design. It consisted of 3 groups, namely group 1 was healthy rats, group 2 was DM rats and group 3 was DM rats treated with MSC-WJ. This study conducted in vivo experiments on alloxan-induced diabetic rat models by testing fasting blood glucose (FBG), serum MDA levels, and catalase activity. Malondialdehyde (MDA) was measured by the Ohkawa method, and catalase activity (CAT) was measured by a modified Sinha method.Results: The results showed the correlation analysis between fasting blood sugar levels and MDA levels (r = 0.697) and catalase activity (r = -0.850) in type 1 DM rats after being treated with Mesenchymal Stem Cell Wharton's Jelly.Conclusion: This study shows a strong positive correlation between fasting blood sugar levels and oxidative stress and a very strong correlation between fasting blood sugar levels and catalase activity of type 1 DM rats treated with MSC-WJ.